ANALISIS FRAUD PENTAGON DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN: Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Periode Tahun 2014-2018 - Novi Anjar Purwaningtyas; Sri Ayem (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to see the effect of Pentagon fraud on reporting fraudulent financial statements.The variables of this research are Pentagon Fraud which consists of financial stability, external pressure, financial targets, nature of the industry, ineffective monitoring, auditor turnover cycle, audit opinion, total accruals, changes in directors, number of CEO photos installed, number of CEO photos installed. , dualism of positions, good corporate governance and fraudulent financial statements. The sampling technique was purposive sampling. Secondary data sources. The data collection method uses the documentary method. The analysis technique used is logistic regression analysis with a significance level of 5 percent. The results showed that financial targets, external certainty, political relations, have a positive and significant effect on fraudulent financial statements. Good Corporate Governance has a negative and significant effect on fraudulent financial statements. Financial stability, external guarantees, ineffective monitoring, CEO image, dualism of positions, audit opinion have no significant positive effect on fraudulent financial statements. The nature of the industry, the change of auditors, the change of directors and TATA have a negative and insignificant effect on fraudulent financial reports. Pentagon fraud affected the fraudulent financial statements by 89.4 percent. 10.6 percent The remaining 10.6 percent other supporting factors are not included in this research model.